2011
DOI: 10.1016/j.jelekin.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Alternative methods of normalising EMG during running

Abstract: We evaluated possible methods of normalising EMG measured during running. MVC, Sprint and 70% Peak Running Speed methods were evaluated and their repeatability, reliability and sensitivity to incremental running speed were compared. Twelve runners performed the same experimental protocol on three separate occasions. Each day, subjects firstly performed MVCs, followed by a 20 m maximal sprint (with a 20-30 m run-up). Following this, they performed the peak running speed (PRS) test until exhaustion. After which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 37 publications
2
73
1
2
Order By: Relevance
“…Numerous studies have attempted to compare EMG normalisation methods, the majority of which have been conducted on healthy controls [6,10] Results showed that although both normalisation methods resulted in predominantly higher normalised EMG amplitude in the hip OA group, a greater number of significant between-group differences were identified using MVIC normalisation, particularly in the Step exercises. Amplitudes were more comparable between groups using PDM normalisation, resulting in significant betweengroup differences only in the Squat exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have attempted to compare EMG normalisation methods, the majority of which have been conducted on healthy controls [6,10] Results showed that although both normalisation methods resulted in predominantly higher normalised EMG amplitude in the hip OA group, a greater number of significant between-group differences were identified using MVIC normalisation, particularly in the Step exercises. Amplitudes were more comparable between groups using PDM normalisation, resulting in significant betweengroup differences only in the Squat exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have attempted to compare EMG normalisation methods, the majority of which have been conducted on healthy controls [6,10] so extrapolation to populations with pathology is limited. Although, there appears to be no consensus regarding the best methods, a comprehensive review by Burden [6] recommended that task normalization methods such as PDM and MDM methods were preferable to MVIC methods to reduce inter-individual variation in healthy controls, but of limited value when comparing across studies or when reapplication of electrodes is required.…”
Section: Discussionmentioning
confidence: 99%
“…• knee extension, knee flexed 90°, hip flexed 90° (sitting) [38,43] • knee extension, knee flexed 60°, hip flexed 90° (sitting) [44,45] • knee extension, knee flexed 45° (sitting) [37] vastus medialis • knee extension, knee flexed 60° (sitting) [44,45] • knee extension, knee flexed 90°, hip flexed 90° (sitting) [43] rectus femoris • knee extension, knee flexed 90°, hip flexed 80° to 90° (sitting) [35,36,38,43] • knee extension, knee flexed 60°, hip flexed 90° (sitting) [44][45][46] lateral hamstring (biceps femoris) long head…”
Section: Muscles Investigated Manual Muscle Test Vastus Lateralismentioning
confidence: 99%
“…• knee flexion, knee flexed 90°, hip flexed 90° (sitting) [38] • knee flexion, knee flexed 60° (sitting) [44,46] • knee flexion, knee flexed 60° (prone) [45] • knee flexion, knee flexed 90°, hands clasped behind head (prone) [37] gastrocnemius lateralis…”
Section: Muscles Investigated Manual Muscle Test Vastus Lateralismentioning
confidence: 99%
See 1 more Smart Citation